2015
DOI: 10.1097/md.0000000000001197
|View full text |Cite
|
Sign up to set email alerts
|

Renal Vein Thrombosis in a Newborn With Abnormal Factor VIII Level

Abstract: Renal vein thrombosis (RVT) in neonates is a rare condition of low mortality but significant morbidity due to renal impairment.We report the case of a male term newborn with left RVT and elevated serum factor VIII (FVIII).The main symptoms of the patient and the important clinical findings: prompt diagnosis of RVT was possible because the classic clinical presentation of macroscopic hematuria, thrombocytopenia, and palpable flank mass were present in this newborn infant.The main diagnoses: finally, the reason … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 11 publications
0
3
0
4
Order By: Relevance
“…[2] Incidence of occlusion is more for left kidney. [3,5,6] Our case was a male child with RVT on right side. Most common associated causes in decreasing order of incidence are prematurity (54%), central venous lines (17%), diabetic mother (13%), asphyxia (6%) and infections (6%) according to a study conducted in 2004.…”
Section: Discussion Of Managementmentioning
confidence: 89%
See 1 more Smart Citation
“…[2] Incidence of occlusion is more for left kidney. [3,5,6] Our case was a male child with RVT on right side. Most common associated causes in decreasing order of incidence are prematurity (54%), central venous lines (17%), diabetic mother (13%), asphyxia (6%) and infections (6%) according to a study conducted in 2004.…”
Section: Discussion Of Managementmentioning
confidence: 89%
“…A study conducted in 2015 has shown that damage to kidney due to poor perfusion resulted in poor prognosis. [6]…”
Section: Discussion Of Managementmentioning
confidence: 99%
“…16 In this study, the activities of FVIII/XI/XIII were investigated in patients with history of artificial joints replacement surgery. The activities of FVIII/XI were found higher in cases compared with controls, which suggested that increased activities of these factors would be risk factors for DVT formation.…”
Section: Discussionmentioning
confidence: 99%
“…La trombosis venosa renal neonatal, entidad relacionada y posiblemente superpuesta, es relativamente común, con una incidencia de 2,2 por 100 000 nacidos vivos y alcanza 13 por 100 000 nacidos vivos en neonatos prematuros (3) . Factores predisponentes como deshidratación, sepsis, asfixia perinatal, policitemia y defectos congénitos de vena renal producen disminución del flujo sanguíneo renal, aumento de la viscosidad de la sangre e hipercoagulabilidad adquirida (4,5) .…”
Section: Discussionunclassified
“…Las causas de la trombosis renal siguen siendo poco claras. Su doble circulación capilar es particularmente vulnerable a la trombosis si se conjugan reducción del flujo sanguíneo renal, aumento de la viscosidad sanguínea e hipercoagulabilidad adquirida (4,6) . Esto último facilita la formación de un coágulo en las venas renales que se puede prolongar a la vena cava inferior.…”
Section: Discussionunclassified